Management of Septic Shock Secondary to Submandibular Phlegmon and Ventilator-Associated Pneumonia in the Intensive Care Unit - Hutasuhut, Afrizal F.; Rismawan , Budiana (CoinReads Media Prima, 2025)
Introduction: Septic shock secondary to submandibular phlegmon, a severe deep neck infection, is a life-threatening condition requiring urgent intervention in the intensive care unit (ICU). When complicated by ventilator-associated pneumonia (VAP), a common nosocomial infection, it significantly increases morbidity and mortality risks. Effective management necessitates rapid source control, targeted antimicrobial therapy, and comprehensive supportive care to address the complex pathophysiology of septic shock and prevent further complications. This case report elucidates the clinical approach to managing septic shock due to submandibular phlegmon complicated by VAP in the ICU. Case Description: A 62-year-old male presented with septic shock secondary to a submandibular phlegmon, characterized by neck swelling, fever, and hemodynamic instability. Initial management included fluid resuscitation, norepinephrine, and empirical antibiotics (meropenem and vancomycin). Surgical drainage of the phlegmon was performed within six hours of admission, revealing extensive purulent material. On day three of ICU care, the patient developed VAP, confirmed by chest X-ray and endotracheal aspirate cultures positive for Pseudomonas aeruginosa. Antibiotic therapy was adjusted based on susceptibility, and lung-protective ventilation was employed. Multidisciplinary care, including fluid optimization, analgesia, and nutritional support, facilitated recovery, with extubation on day seven and ICU discharge on day ten. Conclusion: Successful management of septic shock due to submandibular phlegmon and VAP hinges on early source control, tailored antimicrobial therapy, and meticulous ICU supportive care. This case underscores the importance of multidisciplinary strategies to mitigate complications and improve outcomes in critically ill patients.